The Sentinel At The Bedside: Critical Evaluation Of The Nurse's Role In Early Detection Of Sepsis Based On Protocol Effectiveness And Clinical Acumen (The Review of Diabetic Studies, 2024)
Background: Sepsis is a worldwide public health priority in which patient outcomes are increasingly dependent on early detection. Nurses, being the most regular healthcare providers to have contact with patients, are the key sentinels of detection in this endeavor. The modern challenge is to properly balance the integration of standardized screening protocols with the irreplaceable factor of nursing clinical judgment.Methods: This review synthesizes 2014-2024 to analyze the nurse's role in the early identification of sepsis. It critically evaluates the efficacy of standardized screening tools like NEWS and qSOFA across various settings and the interplay between protocol-driven care and clinical acumen.Results: Evidence exists that while tools like NEWS provide a critical, sensitive safety net, they can be non-specific and cause alert fatigue. Alternatively, qSOFA, though specific, is poor in sensitivity and thus may result in a missed diagnosis. The nurse's function transcends calculation to interpretation of trends, triggering rapid response and care coordination. The primary observation is that no single strategy of rigid protocol adherence or unaided clinical judgment is sufficient. The optimal detection is with a synergistic model where evidence-based tools structure and facilitate the nurse's logical and intuitive reasoning, particularly for complex cases in atypical populations.Conclusion: The optimal sepsis defense is an empowered, critically thinking nurse enabled by intelligent technology and a culture of psychological safety. All future efforts must be in the domains of education, human-centered technology development, and research into next-generation context-aware technologies.